Contextual Analysis of Electronic Cosmetics Advertisements: A Semantic Study - Lect: Ali Flayyih Hasan (Journal of College of Education, 2024)
The present study examines semantic textual features used in electronic, cosmetic advertisements to manipulate customers. The study adapts Leech's semantic theory (1981) to analyze the meanings that appear in advertisements. The data is gathered from six official sites of international cosmetic companies such as  (l'oréal, Nivea, Neutriherbs,   Covergirl, Twasa, and LUX). The study concludes that the semantic features appearing in electronic cosmetics advertisements are divided into three main categories. Conceptual, thematic, and associative meaning. Associative meanings are divided into five subcategories:  connotative, stylistic, emotive, reflective, and collective meanings. Furthermore, the study reveals that electronic cosmetics advertisements' semantic features are informative and persuasive. The study concludes that the types of meaning used in these advertisements are instrumental in fostering successful communication between the costumer and the advertiser.
Keywords: cosmetics, manipulation, Semantics, commercial advertisements and beauty